Pentobarbital Coma Use in a Pregnant Patient With Refractory Intracranial Hypertension: A Case Report. Issue 2 (March 2022) - Patel, Devan; Dehne, Kelly; Pajer, Hengameh; Barnett, Randaline; Sasaki-Adams, Deanna; Quinsey, Carolyn
Abstract : Objective: Intracranial hypertension is a life-threatening condition that requires emergent diagnosis and management. Although pentobarbital coma for refractory intracranial hypertension has been studied in the general population, this study is the first reported case of pentobarbital coma use in a pregnant patient. Methods: We performed a retrospective chart review of a pregnant patient with refractory intracranial hypertension and reviewed the current literature on the role of pentobarbital coma. Results: We present the case of a 35-year-old woman at 26 weeks of gestation who developed refractory intracranial hypertension secondary to rupture of a dural arteriovenous fistula. The patient was taken to surgery for decompressive hemicraniectomy, clot evacuation, and dural arteriovenous fistula resection. Subsequently, the patient was treated with pentobarbital coma for 5 days and achieved adequate control of her intracranial pressures. The patient and fetus were closely monitored by the obstetrics team with no apparent harm to fetal well-being during her hospital stay. The patient underwent planned cesarean delivery at term, and both the mother and newborn were discharged in stable condition with no known pentobarbital-related complications. Conclusions: Thus, we present the first case report demonstrating that pentobarbital coma may be a safe and efficacious option for treating pregnant patients with life-threatening refractory intracranial hypertension. We also provide dosing information for pentobarbital administration. Additional studies and reports involving pregnant patients are needed to better understand the impact of pentobarbital on both the mother and fetus. Furthermore, long-term follow-up of both the mother and newborn is critical to identifying any delayed sequelae of neonatal exposure to pentobarbital.